Postinfection control by bacteriophage T4 of Escherichia coli recBC nuclease activity. - Behme, M T (1976)
Infection by bacteriophage T4 has previously been shown to cause a rapid inhibition of the host recBC DNase, an ATP-dependent DNase that is required for genetic recombination in Escherichia coli. We report here the partial purification of a protein ("T4 rec inhibitor") from extracts of T4-infected cells and some characteristics of the in vitro inhibition reaction with purified inhibitor and recBC nuclease. This inhibitory activity could not be purified from extracts of uninfected E. coli. Both the ATP-dependent exonuclease and DNA-dependent ATPase activities of recBC DNase are inhibited by T4 rec inhibitor. Experiments suggest that the inhibitor interacts with the nuclease in a stoichiometric manner. The biological significance of this inhibition is discussed with respect to control reactions in phage-infected cells.